TINJAUAN PUSTAKA: LATIHAN BEBAN PADA CABANG OLAHRAGA RENANG - Nurhayati Simatupang; Fathia Ihza Nurfati; Dina Agustina Sitorus; Fransiskus Samosir; Jona Lamtama Sihotang (Universitas Muhammadiyah Cirebon, 2026)
Swimming requires good physical condition because movements in the water require coordination between the arms and legs, breathing, and efficient technique. The purpose of this study was to determine the role of weight training in swimming based on previous research. The method used in this study was a Systematic Literature Review by examining journal articles published between 2021 and 2025. This literature review was used because this study requires data from various literature sources, particularly scientific articles discussing resistance training, strength training, and swimming performance. Based on the results of the review of several articles, weight training has a positive effect on improving swimming performance, especially in aspects of arm muscle strength, leg muscle strength, explosive power, muscular endurance, and swimming speed. Forms of exercise that can be used include push-ups, pull-ups, pull-downs, squats, alternate squats, resistance bands, jump ropes, hand paddles, swim tether belts, and water rubber around the waist. Resistance training must be structured, planned, and sustained to support the athlete's physical abilities and optimally improve swimming performance